Selection of LED lighting systems for the reduction of the biodeterioration of speleothems induced by photosynthetic biofilms in the Nerja Cave (Malaga, Spain) - Muñoz-Fernández, Juan; Del Rosal Padial, Yolanda Remedios; Álvarez-Gómez, Félix; Hernández Mariné, Mariona; Guzmán-Sepúlveda, Rafael; Korbee-Peinado, Nathalie; López-Figueroa, Félix (Elsevier, 2021)
Electrical lighting favours the development of photosynthetic biofilms in caves which can induce biodeterioration in the colonized substrates. The use of specific lights as a limiting factor for biofilm growth could be effective in their control and represents an alternative to chemical methods since they can damage the substrate. However, studies about lighting and the photosynthetic activity of organisms in caves are scarce. In order to select the most effective LED light source in reducing photosynthesis and therefore, in reducing the growth rates of microalgae and cyanobacteria, four biofilms in the Nerja Cave were illuminated by several light emitted diodes (LEDs) with different spectral compositions and the photobiological responses were measured both by empirical and theoretical methodologies. The empirical approach was based on the photosynthetic efficiency, by measuring the in vivo chlorophyll a (Chl a) fluorescence and the theoretical approach was based on the photonic assimilation performance related to the proportion of the light quality used for photosynthesis, according to the action spectra for photosynthesis available in the literature. The photobiological responses showed differences between the empirical and theoretical approach mainly in biofilms dominated by cyanobacteria and red algae, probably because the available action spectra were not useful for monitoring these Nerja Cave biofilms. However, the expected spectral responses of photosynthesis were observed in green microalgal biofilms with maximum photosynthetic efficiency in red and blue light although the green light was also unexpectedly high. The high photosynthetic efficiency in green light could be explained by the predictable high chlorophyll content due to a very dark environment. The results were not conclusive enough for all the biofilm types to be able to recommend a specific lighting system for the photocontrol of biofilm expansion. (...)
Keywords: Biopelículas; Diodos emisores de luz; Algae; Cyanobacteria; Biofilms; LEDs; Photonic assimilation performance; Photosynthetic efficiency